FUNCTIONAL AND MORPHOLOGICAL OUTCOMES OF THE INVERTED INTERNAL LIMITING MEMBRANE FLAP TECHNIQUE IN SMALL-SIZED AND MEDIUM-SIZED MACULAR HOLES <400 µm. Issue 10 (October 2021) - Baumann, Carmen; Dervenis, Nikolaos; Kirchmair, Katharina; Lohmann, Chris P.; Kaye, Stephen B.; Sandinha, Maria T.
Abstract : Purpose: To assess the effect of an internal limiting membrane flap (IF) in macular hole surgery on the best-corrected visual acuity (BCVA) and integrity of the ellipsoid zone (EZ) and external limiting membrane. Methods: Patients were included who had successful surgery for macular hole <400 µ m with or without an IF. Main outcome measures were BCVA and restoration of the external limiting membrane and EZ at 12 months. Results: Sixty patients were included, 36 with conventional peeling and 24 with an IF. The best-corrected visual acuity improved from 0.74 (±0.30) logarithm of the minimum angle of resolution (20/110 Snellen) to 0.26 (±0.20) (20/36 Snellen) in patients without and from 0.77 (±0.32) logarithm of the minimum angle of resolution (20/118 Snellen) to 0.18 (±0.12) (20/30 Snellen) in patients with an IF, respectively. There was no difference in the integrity of the EZ and external limiting membrane in patients with or without an IF at either 3 ( P = 0.58, P = 0.20), 6 ( P = 0.81, P = 0.10), or 12 months ( P = 0.60, P = 0.20) or in the BCVA at 3 ( P = 0.24), 6 ( P = 0.18) and 12 months ( P = 0.11). In the multivariable model, only preoperative BCVA ( P < 0.01), EZ integrity ( P = 0.001), and age ( P < 0.01) were associated with the post-operative BCVA. Conclusion: In patients undergoing surgery for macular hole <400 µ m, the use of an IF did not affect the BCVA or the integrity of the EZ and external limiting membrane. Abstract : After surgery for macular holes <400 µ m, the best-corrected visual acuity and the integrity of the ellipsoid zone improved significantly between 3 and 12 months, irrespective of the use of an internal limiting membrane flap.